Implikasi Hidup Kekal Terhadap Tujuan Hidup Personal: Analisis Kiasmus Yohanes 12:23-28a - John Marlin; Sukarman Petrus; Paulus Dimas Prabowo (Predica Verbum: Jurnal Teologi dan Misi, 2023)
The writing of this article was motivated by a partial understanding of the concept of eternal life, where believers often only understand it as a matter of the future. In fact, understanding eternal life without having implications for current temporal life will weaken Christianity. John emphasizes in his gospel that the eternal life referred to also touches the present aspects of every believer. The impact can be felt when they live in the world. One of the texts that conveys this is John 12:23-28a. The method used is style analysis, with emphasis on the chiasmus structure. The result obtained is that the chiasm pattern contained in it and this pattern shows that eternal life is the axis that is central in formulating life goals. The purpose of life is: 1) glorifying God through obedience and suffering; 2) carrying out God's mission to reach people who do not yet believe; and 3) serve God with a willingness to follow Him and believe in the promise of glory that will be available in eternity.